Impact of Macroeconomic Factors on Stock Returns of KSE 100 Index - MUHAMMAD TAHIR KHAN; ASAF KHAN; DR. ADNAN AHMAD; OBAID ULLAH BASHIR (Journal of Business & Tourism, 2021)
Positive moment of stock return is an important component for investors, the intension of this study was to examine the impact of macroeconomic variables on stock return. The monthly stocks price data of 15 firms was taken from the period of January 2008 to December 2012. The results revealed that there was a positive impact of exchange rate on stock return, while inflation rate and interest rate had a significant negative impact on stock return. The results of variance decompositions revealed that out of three macroeconomic variables Inflation rate showed greater forecast error for KSE 100 Index